Impact of poor service on hospitality industry organizations: A viewpoint - Fowler, David (Tourism and Hospitality International Journal, 2023)
This short essay study examines the negative impact of perceived poor service within the hospitality industry. This succinct review of the literature reveals that poor service is a precursor for business deterioration and possible failure. Customer satisfaction is crucial to the hospitality industry, which includes companies like hotels, eateries, and other facilities focused on providing services. Bad customer service can negatively affect a consumer's experience and opinion of the brand, which can result in unfavorable reviews, a decline in client loyalty, and ultimately lower sales. Businesses must prioritize providing outstanding service to sustain their reputation and performance in a sector where consumer satisfaction is crucial. Failure to do so could have serious repercussions for the company because negative online and word-of-mouth publicity can spread quickly and harm the company's brand. In this scenario, it is critical to examine the negative effects of subpar service in the hospitality sector and comprehend the steps that companies may take to guarantee the provision of high-quality service.